Review of Women in the Indian Diaspora: Historical Narratives and Contemporary Challenges - Bera, Shreya (AMERICANA E-journal of American Studies in Hungary, 2019)
Women in the Indian Diaspora: Historical Narratives and Contemporary Challenges Edited by Amba Pande 2018 Delhi, India: Springer 200 pp. ISBN: 978-981-10-5950-6